Yaws' critical property data for chemical engineers and chemists - Yaws, Carl L. (Knovel, 2012)
"This database contains over 290,000 data records covering physical, thermophysical, thermodynamic, transport, safety, and environmental properties for over 5,000 inorganic substances and over 35,000 organic substances. The interactive database format provides granular search accessibility and the means for comparison of properties across a wide array of substances. Most interactive tables contain a plotting tool showing properties as a function of variables such as temperature, pressure, and concentration. The tables contain chemical names, their synonyms and molecular formulas for enhanced searchability."--Knovel description.